Asset Based Community Development untuk Membangkitkan UMKM di Lingkup Desa yang Terdampak Pandemi Covid-19 - Christie, Zefanya; Sabrina, Sylvi; Altis, Annisa (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
Every citizen has actually been attached to various rights to himself since birth which are guaranteed and protected by the state. One of the rights of these citizens is economic rights and welfare. The outbreak of the COVID-19 pandemic has affected various aspects of life, one of which is the economic aspect. It takes efforts from various parties, both the government and society, so that the wheels of the Indonesian economy can continue. The existence of Micro, Small and Medium Enterprises (MSMEs) in the community plays an important role in helping the country's economic cycle. This important role is in the form of creating jobs and increasing the Gross Domestic Product (GDP). Therefore, a national economic recovery strategy is needed, especially for MSME players in an applicable and appropriate manner. In this case, the author proposes an asset-based community development program aimed at MSMEs in rural areas. The Asset Based Community Development method aims to explore the potential of available assets and how communities can contribute to realizing a sustainable economic ecosystem. Furthermore, the author will review further the position of MSMEs, the realization of Asset-Based Community Development in other countries, as well as the form of Asset-Based Community Development in reviving MSMEs, especially in rural areas such as stalls affected by the COVID-19 pandemic. This research was conducted using a juridical-empirical method that enforces legal policies according to the conditions of society. As a result, Asset Based Community Development can be used as a post-COVID-19 economic recovery program.